MENGURANGI KONSUMSI ENERGI DENGAN AUDIT DAN MANAJEMEN ENERGI PADA RUANG KENDALI (STUDI KASUS DI PT PWI) - Wawan Gunawan (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2018)
The company is very difficult to reduce operating costs because of the increase in employee wages, the price of raw materials and which is not less important and the effect is the energy price of electricity continues to rise. Energy conservation is one of the efforts in controlling the use of electrical energy without having to reduce the quantity and quality of production.PT. PWI is one of the export-oriented shoe product manufacturing companies, the demand from consumers is increasing every year, especially for the European and American markets, this requires the adequacy of electricity that has high economic value. This research area is office floors and supporting buildings which are referred to as control roomsEnergy audit and management is one method that is often used in companies or government agencies in saving energy use, with the main step of conducting an initial audit of areas and equipment that uses electrical energy, data analysis, detailed audits, monitoring and recommendations for subsequent improvements.Based on the results of the collection of energy consumption intensity data (IKE) in the supporting space in total is 251.56 kWh / m2, meaning that it is still above the standard set of 240 kWh / m2. Potential opportunities for PHE are obtained in areas that have an air conditioning system (AC), namely by replacing the type of refrigerant previously Freon (synthetic) type into the Musicool type. Through the measurement process before and after replacing the type of refrigerant, it is obtained a reduction in energy consumption of 908.170.84 kWh / year, and an efficiency of 64.42 % (rounding results).